Modeling of an HPS for the electric power demand of the cattle farm using genetic algorithm - AKAR, ONUR (My University, 2023)
Today, as the demand for energy increases based on the increasing population and improving technology, resorting to new energy sources has become a necessity. Due to the rapid consumption of fossil fuels and the responsibility of humanity for the environment, Renewable Energy Sources (RES) are of a quality that may respond to this necessity. But the RES such as sun and wind vary depending on the weather conditions. Considering such variance, Hybrid Power Systems (HPS) are suggested in order to assure reliability and continuity in energy generation. For the sake of strengthening the HPS that are dependent on weather conditions, it is considered to increase the system\"s reliability and continuity through the inclusion in the HPS of cattle biomass reserves in the area. In this paper, it was studied on modeling of HPS based on sun, wind and biogas that will meet the electric power demand of the cattle farm located at Afyonkarahisar, Turkey. The two decades\" animal population and load value changes were estimated through Genetic Algorithm (GA), and the HPS model was investigated under different scenarios considering sustainable energy and environment objectives, and the analyses were performed considering the changes in economic parameters.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Biomass; Genetic algorithm; HOMER; Hybrid power system; PV*SOL; PVsyst